1984
DOI: 10.1002/fam.810080402
|View full text |Cite
|
Sign up to set email alerts
|

The performance of various testing columns in small‐scale horizontal burning studies

Abstract: The use of Critical Oxygen Index testing columns in the horizontal configaration is investigated. Gas analysis results &om within columns of simple design indicate that they are unsuitable for burning studies because of entrainment of the external atmosphere and recirculation of combustion products. A new design of colomn and holder is proposed that eliminates these effects and provides B possible means of studying small-scale horizontal combustion in Merent oxygenlnitrogen mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…10% found for reproducibility in the new horizontal test apparatus [1] may actually be a reflection of a lack of consistency in the composition of the test atmosphere. The larger errors detected with combustion experiments using mixtures containing high proportions of oxygen [1] are in keeping with previously reported observations [7].…”
supporting
confidence: 90%
See 3 more Smart Citations
“…10% found for reproducibility in the new horizontal test apparatus [1] may actually be a reflection of a lack of consistency in the composition of the test atmosphere. The larger errors detected with combustion experiments using mixtures containing high proportions of oxygen [1] are in keeping with previously reported observations [7].…”
supporting
confidence: 90%
“…Although our work with horizontal columns was not as extensive as with vertical columns, it was again apparent that both gas composition and velocity can influence the degree of entrainment [7]. We demonstrated that an open-ended column of the type used by Vanspeybroeck et al exhibits significantly more entrainment of the external atmosphere than a restricted outlet column of equivalent diameter.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…These two last quantities depend on the effective heat transfer coefficient h c . This dependence on the heat transfer coefficient explains the variation of the LOI with the sample dimensions [17], the gas velocity [18] or the equipment dimensions [19,20] and the difficulty to relate LOI to intermediate-and large-scale fires.…”
Section: Determination Of Loimentioning
confidence: 99%